Union-Management Relations in Canada, 3rd edition - Rose, Joseph B. (Relations industrielles / Industrial Relations, 1996)
The article reviews the book, "Union-Management Relations in Canada," 3rd edition, by Morley Gunderson and Allen Ponak.
Keywords: Book reviews; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Labor Unions; Labor relations; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z